Pengaruh Konsentrasi Larutan AB Mix Terhadap Pertumbuhan dan Produksi Mentimun (Cucumis sativus L.) pada Sistem Hidroponik NFT (Nutrient Film Technique) - Yulita, Yulita; Amelia, Kiki; Putri, Santi Diana; Sari, Wilna (UNIVERSITAS LABUHANBATU, 2024)
Cucumber (Cucumis sativus L.) is one of the fruit vegetables that is widely consumed by the people of Indonesia. The low production of cucumber in Indonesia is caused by several factors including climatic factors, farming methods such as tillage, fertilization, irrigation, and pests and diseases. The right solution to overcome these problems and increase cucumber production in Indonesia is the Hydroponic farming technique. Hydroponics is a way of growing plants without using soil as a place to grow plants but using water or other porous materials such as gravel, sand, husk charcoal and tile fragments as planting media. Hydroponic cultivation uses AB Mix solution as a source of nutrients for plants. AB Mix solution is a specially formulated fertilizer from mineral salts that can be dissolved in water containing important nutrients needed by hydroponic plants. This research was conducted from May to August 2023. The research was conducted at Blasta Urban Farming Padang which is located at Jl. Bunda Raya No. 6 Ulak karang Utara, Padang. The design used in this study was a Completely Randomized Design (CRD) with 3 treatments and 10 replicates so that 30 experimental samples were obtained. The treatments given in this study were A = 250 ml nutrient + water (800 ppm), B = 150 ml nutrient + water (400 ppm), C = 400 ml nutrient + water (1,200 ppm). The research data were analyzed using anova table and continued with BNJ further test. The parameters observed were flower emergence time, plant height, number of leaves, number of flowers per plant, number of fruits per plant, weight per fruit. Keywords: ab mix solution concentration, cucumber, hydroponic